The development of circle kit for form 2 circle topic - Mohd Zulkiflee, Amirah Fatihah; Arbin, Norazman; Kamarudin, Norsyazana; Mohd Razali, Siti Noor Asyikin (Universiti Pendidikan Sultan Idris, 2025)
The aim of this study is to develop and evaluate the validity and usability of Circle Kit for the Form 2 Circles topic. The study employs the Design and Development Research (DDR) approach, focusing on the Analysis Phase and the Design and Development Phase guided by the ADDIE model. Five experts consisting of four Mathematics lecturers from a public university and one secondary school Mathematics teacher, assessed the kit’s validity. To determine usability, 35 Mathematics trainee teachers from Universiti Pendidikan Sultan Idris (UPSI) were selected through simple random sampling and responded to a usability questionnaire. Data from expert evaluation were analysed using descriptive analysis, employing the Content Validity Index (CVI), while usability was determined using the mean score. The results of the study found that the validity of the content of daily lesson plan (RPH), kit face and kit content is satisfactory with a value of CVI 1.00. The results also show that the kit’s usability scored a mean of 3.83, indicating high usability. In conclusion, the RPH aligns with the learning standards and supports the kit’s use during Teaching and Facilating (PdPc) sessions. The implication is that the developed kit effectively addresses the Circles topic, making it suitable as a teaching aid (BBM). This study provides valuable guidelines and innovative ideas for Form 2 Mathematics teachers to enhance their teaching through the application of this educational tool.